Enhanced Rotational Stability with the Locking Anchor EndoButton System: A Biomechanical Comparison of Free Bone Graft Non-Screw Methods for Anterior Shoulder Instability - Tosun, Muhammed Furkan; Oklaz, Ethem Burak; Kaya, İbrahim; Erbay Elibol, Fatma Kübra; Perdeci, Elif Naz; Demir, Teyfik; Tolunay, Tolga; Kanatlı, Ulunay (Clinics in orthopedic surgery, 2025)
Background: Despite the increasing use of non-screw free bone graft fixation methods for glenoid defects associated with anterior shoulder instability, biomechanical knowledge of their effectiveness remains limited. This study aims to evaluate the biomechanical stability of different non-screw iliac crest graft fixation methods for anterior shoulder instability. Methods: Forty-eight scapula bone models were used to compare the mechanical properties of non-screw fixation methods. The samples were divided into 4 groups: group 1 with 2 anchors, group 2 with 2 EndoButtons, group 3 with a combination of 2 anchors and 1 EndoButton, and group 4 with the Locking Anchor EndoButton System (LAES). Following fixation, dynamic testing began with a 10-N preload. After the preload, cyclic loading was applied between 10 N and 150 N for 100 cycles. Static loading was then conducted at a rate of 0.08 mm/sec. The test continued until either system failure occurred or the graft displacement reached 7 mm. Stiffness and maximum load values were determined. Rotational tests were performed at an angular velocity of 10°/sec. Torsional stiffness and maximum torque capacity were determined. Results: Under dynamic loading conditions, the LAES group exhibited significantly less displacement compared to all other groups, while no significant differences were observed among the remaining groups. In static testing, the LAES group demonstrated the highest stiffness (183.354 ± 33.295 N/mm), significantly exceeding that of the Anchor group (93.847 ± 20.401 N/mm) and Anchor- EndoButton group (135.036 ± 37.815 N/mm). The EndoButton and LAES groups withstood significantly higher maximum loads than the Anchor and Anchor-EndoButton groups, with the LAES group achieving the highest load capacity (543.333 ± 100.851 N). In rotational testing, the LAES group displayed significantly greater torsional stiffness (0.182 ± 0.063 N·m/°) compared to all other groups. Additionally, the LAES group withstood the highest maximum torque (3.068 ± 1.194 N·m), significantly surpassing the Anchor, EndoButton, and Anchor-EndoButton groups. Conclusions: All tested fixation methods provided sufficient stability under early postoperative loading conditions. However, the LAES demonstrated superior biomechanical performance, particularly in terms of rotational stability, compared to other non-screw fixation techniques. KCI Citation Count: 0